Microwave Absorbent Packaging Material from Composites Chitosan-Polyvinyl Alcohol Polymer - Bambang - Riyanto; Akhiruddin - Maddu; Esa Ghanim Fadhallah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Microwave absorbent packaging materials currently tend to biomaterial. Chitosan is a dielectric biomaterial with polycationic properties. The aim of this study was to analyze characteristics of microwave absorbing packaging material made from composite chitosan-polyvinyl alcohol (PVA) polymer. The ability of the packaging material to absorb microwave was determined by reflection loss measurement. Formed packaging prototype resembles as a thin transparent yellowish plastic with thickness (0.11-0.22 mm) and the tensile strength (106.33±2.82-143.00±2.59 kPa). SEM analysis showed homogenous structure characterized by interaction between chitosan and PVA. Optimum absorption value was obtained from chitosan concentration of 1%, with average value of reflection loss was (-31.9289±4.0094) dB.Keywords: chitosan, material packaging, microwave, reflection loss